Business and human rights : beyond the end of the beginning - Rodríguez Garavito, César A. (Globalization and human rights (Cambridge, England), 2017)
"The Center for Law, Justice and Society (Dejusticia), a human rights research and advocacy organization based in Bogota, Colombia, was the home base of the project and provided much of the intellectual and organizational impetus for the book. I am particularly grateful to Dejusticia members who have staffed our business and human rights area (Meghan Morris, Sean Luna, Claret Vargas, and Tatiana Andia) for their superb research assistance and key contribution to establishing Dejusticia's voice in the global discussion on business and human rights"--